Performance Evaluation of An Innovative-Vapor- Compression-Desalination System - Mirna R. Lubis,; Mark T Holtzaple (Aceh International Journal of Science and Technology, 2012)
Abstract – Two dominant desalination methods are reverse osmosis (RO) and multi-stage flash (MSF). RO requires large capital investment and maintenance, whereas MSF is too energy-intensive. Innovative system of vapor compression desalination is proposed in this study. Comprehensive mathematics model for evaporator is also described. From literature study, it is indicated that very high overall-heat-transfer coefficient for evaporator can be obtained at specific condition by using dropwise condensation in the steam side, and pool boiling in the liquid side. Smooth titanium surface is selected in order to increase dropwise condensation, and resist corrosion. To maximize energy efficiency, a cogeneration scheme of a combined cycle consisting of gas turbine, boiler heat recovery, and steam turbine that drives compressor is used. The resource for combined cycle is relatively too high for the compressor requirement. Excess power can be used to generate electricity for internal and/or external consumptions, and sold to open market. Four evaporator stages are used. Evaporator is fed by seawater, with assumption of 3.5% salt contents. Boiling brine (7% salt) is boiled in low pressure side of the heat exchanger, and condensed vapor is condensed in high pressure side of the heat exchanger. Condensed steam flows at velocity of 1.52 m/s, so that it maximize the heat transfer coefficient. This unit is designed in order to produce 10 million gallon/day, and assumed it is financed with 5%, 30 years of passive obligation. Three cases are evaluated in order to determine recommended condition to obtain the lowest fixed capital investment. Based on the evaluation, it is possible to establish four-stage unit of mechanical vapor compression distillation with capital $31,723,885. Keywords: Desalination, dropwise condensation, heat exchanger, StarRotor compressor, vapor compression distillation.